A study on the factors that influence employees motivation among non-academic employees at Universiti Tun Hussein Onn Malaysia (UTHM) / Nurfazreena Mohd Sah - Mohd Sah, Nurfazreena (Faculty of Business and Management, 2014)
Nowadays, many organizations are competing each other to become success and excellent. When the employees are motivated during do their task, it become the one of the competitive advantage for the company. However, nowadays employees are likely tend to have the intention to leave the organization due to it is hard for them to be promoted. So, to increase their level of motivation there are many factors that that will influence the motivation of employees that had been found by the previous research including work security, safety and rewards. This study also is focusing on the factors that contribute the level of motivation. The main purpose of this study are to observe three things which are the level of motivation, the relationship between motivation and the independent variables (rewards, work environment, employee participation, communication and training) and identify the most factors that will influence the motivation. The study of motivation of employees is important and give the benefit to both parties which the employees and employers. All the data are measured by using SPSS to analyze the data through Reliability Analysis, Frequency Analysis, Descriptive Analysis, Pearson Correlation Analysis and Regression Analysis. The study was conducted among non-academic employees at Universiti Tun Hussein Onn Malaysia (UTHM) where the numbers of employees is 1174 while the number of respondent used in this study is 291 employees. The results obtain in this study shows that all the variable have significant relationship with motivation and the most factors that will influence employee’s motivation is work environment. As the work environment is the most influential factors, the organization should take initiative to increase the safety in the works place as the employees will feels comfortable.